Youths' history of the United States in verse : to which is added a valuable chapter on the great inventions of all ages, also the Declaration of Independence in the same style ; designed to convey instruction to the young in an attractive form, and to place within the reach of adults of all classes the means of aquiring and easily retaining in the memory all the important facts of history (Carlon & Hollenbeck, 1883)
Text is a series of questions followed by the answer in verse.